Optoelectronics of organic nanofibers formed by co-assembly of porphyrin and perylenediimide - Li, Yuangang (2014)
Organic nanofibers are formed by simple ionic co-assembly of positively charged porphyrin (electron donor) and negatively charged perylenediimide (electron acceptor) derivatives in aqueous solution. Two kinds of electron transfer routes between electron donor and electron acceptor under light excitation in nanofibers are confirmed by DFT calculations and experimental data.